The Impact of implant-based reconstruction on persistent pain after breast cancer surgery: A systematic review. Issue 2 (February 2022) - Guliyeva, Gunel; Torres, Ricardo A.; Avila, Francisco R.; Kaplan, Jamie L.; Lu, Xiaona; Forte, Antonio J.
Summary: Introduction: With the increasing number of breast cancer survivors and reconstruction operations, persistent pain following breast cancer surgery (PPBCT) and its management is becoming a challenge for plastic surgeons. To date, most studies compared the difference in the level of PPBCT in reconstruction versus nonreconstruction groups. We systematically reviewed the literature to assess the impact of implant-based reconstruction on PPBCT levels. Materials and methods: PubMed, Embase, CINAHL, and Scopus databases were searched for relevant articles. We used five search strategies: (persistent pain after breast cancer surgery AND reconstruction), (chronic postsurgical pain AND breast reconstruction), (Breast Implantation [MeSH Terms] AND "Chronic Pain" [MeSH Terms]), (breast reconstruction AND chronic pain), and (postmastectomy pain syndrome AND breast reconstruction). Results: A total of 2281 articles were detected. After scanning for the title and abstract, full-text articles were reviewed to identify the eligible articles. Eleven articles were included in the final review, with seven of these reporting no increased chance of PPBCT following reconstruction with implants, whereas two articles described lower chances of PPBCT following implant-based reconstruction. Conclusion: We discovered that implant-based reconstruction does not increase the risk of PPBCT in comparison to other surgical techniques or mastectomy alone. This relationship may facilitate doctors and their patients in the decision-making of the appropriate reconstruction technique to use. In addition, our results should prompt plastic surgeons to prescribe the same dosage and frequency of analgesics to patients undergoing implant reconstruction as they would to their patients not undergoing reconstruction.